2008
DOI: 10.1346/ccmn.2008.0560611
|View full text |Cite
|
Sign up to set email alerts
|

Clay Minerals in Basalt-Hawaiite Rocks From Mururoa Atoll (French Polynesia). I. Mineralogy

Abstract: Clay minerals in chilled or brecciated margins (altered glass) and massive inner crystalline parts (mesostasis) of three basalt-hawaiite bodies from Mururoa Atoll (French Polynesia) have been studied in order to compare their chemical and mineralogical compositions. Polyphase assemblages comprise di- and trioctahedral phases, both of which consist of non-expandable layers (chlorite, celadonite) and two types of expandable layers (saponite and Fe-rich smectite or ‘nontronite-like’ material). The presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…These phyllosilicates are aluminum-rich and unlikely to be abundant in the primitive altered oceanic crust of the Hadean. The Hadean seafloor was mainly formed of mafic and ultramafic rocks, such as basalt, komatiite and peridotite, which hydrothermal alteration has been widely studied through (i) petrological and mineralogical observations of samples collected in oceanic hydrothermal settings (Alt and Honnorez, 1984;Buatier et al, 1993;Hunter et al, 1999;Buatier et al, 2001;Alt and Teagle, 2003;Dias and Barriga, 2006;Lackschewitz et al, 2006;Mas et al, 2008); (ii) experimental alteration of bulk rocks (Humphris, 1978;Mottl and Holland, 1978;Mottl et al, 1979;Seyfried and Bischoff, 1979;Seyfried and Dibble, 1980;Seyfried and Bischoff, 1981;Seyfried and Mottl, 1982;Marcaillou, 2011;Lazar et al, 2012); and (iii) mineral evolution (Hazen et al, 2008;Hazen and Sverjensky, 2010;Hazen, 2013;Hazen et al, 2013). All above studies suggested that Fe-Mg rich phyllosilicates along with various oxides, hydroxides, anhydrites and sulfides are the major alteration minerals formed.…”
Section: Introductionmentioning
confidence: 99%
“…These phyllosilicates are aluminum-rich and unlikely to be abundant in the primitive altered oceanic crust of the Hadean. The Hadean seafloor was mainly formed of mafic and ultramafic rocks, such as basalt, komatiite and peridotite, which hydrothermal alteration has been widely studied through (i) petrological and mineralogical observations of samples collected in oceanic hydrothermal settings (Alt and Honnorez, 1984;Buatier et al, 1993;Hunter et al, 1999;Buatier et al, 2001;Alt and Teagle, 2003;Dias and Barriga, 2006;Lackschewitz et al, 2006;Mas et al, 2008); (ii) experimental alteration of bulk rocks (Humphris, 1978;Mottl and Holland, 1978;Mottl et al, 1979;Seyfried and Bischoff, 1979;Seyfried and Dibble, 1980;Seyfried and Bischoff, 1981;Seyfried and Mottl, 1982;Marcaillou, 2011;Lazar et al, 2012); and (iii) mineral evolution (Hazen et al, 2008;Hazen and Sverjensky, 2010;Hazen, 2013;Hazen et al, 2013). All above studies suggested that Fe-Mg rich phyllosilicates along with various oxides, hydroxides, anhydrites and sulfides are the major alteration minerals formed.…”
Section: Introductionmentioning
confidence: 99%
“…However, because this unknown hydrous mineral is enriched with iron in EMP analysis and associated with iron-rich saponite, it may be a ferric rich member of smectite, nontronite. Nontronite can be produced by saponite oxidation; however, it is still an undetermined mineral and is named as nontronite-like mineral in this study (Mas et al, 2008). Conclusively, dolomite, magnesite, diopside and spinel can only be identified by EMP although there are suspicious peaks in some cases; the chemical variation of carbonates are also mainly determined by EMP; and calcite, saponite, mica, serpentine, forsterite and enstatite show observable signals in XRD.…”
Section: Serpentinizationmentioning
confidence: 70%
“…Mas et al (2008) show that subaerial, submarine lava flows and dyke exhibit all chilled thin vitreous margins ( Fig. 2a) contrasting with a thick inner part which is highly crystallized (Fig.…”
Section: Mesostasis and Columnar Jointsmentioning
confidence: 99%
“…The average size of mesostasis micro-settings can be represented by a square of 50 µm side. According to Mas et al (2008), there are about 50 to 100 sites observable on a single thin section of Mururoa basalt (30×40 mm). In other words, 8 × 10 4 to 16 × 10 4 clay micro- settings per square meter are outcropping on any surface crosscutting the crystallized inner parts of the basalt lava bodies.…”
Section: Properties Of the Clay-rich Surfaces Exposed To Solutionsmentioning
confidence: 99%